Rancang Bangun Sistem Informasi Klinik Gigi Berbasis Web Pada Klinik Riona Dental Care - Mahfuzan Hadi Wicaksono; Salhazan Nasution (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The process of collecting information such as patient data, medical records and inventory at the Riona Dental Care Clinic are still using manual system. This has led to delays in creating, searching, and delivering information on medical records and inventory. Thus, it needs a capable system using web-based technology that can be improve health services and facilitate the management of medical records and inventory. The system is developed using CodeIgniter framework and MySQL database. This system design method uses Waterfall model which consists requirement analysis, system design, implementation, integration and system testing, and maintenance. The techniques used to perform system testing is black-box testing. The result of the testing stated that the system is free from syntax errors so that it can be said that the system is functionally running sufficiently good and in accordance with system requirements and produce output in accordance with what is expected. Keywords: information system, medical record, patient, web